Inorganic fullerene-like tungsten disulfide/waterborne polyurethane reinforced Spectra® composites with improved mechanical properties and tensile energy absorption - Shuangyan Wu; Gajanan S. Bhat (Results in Materials, 2023)
Fiber-based nanocomposites play a significant role in bullet-resistant, anti-impact, and aerospace applications. This research was conducted to (1) determine the feasibility of preparing inorganic fullerene-like tungsten disulfide (IF-WS2)/waterborne-polyurethane (WPU) dispersions in varying water/ethanol mediums and (2) study the effects of IF-WS2/WPU impregnation on mechanical and tensile energy absorption properties of ultra-high molecular weight polyethylene (UHMWPE) fibers. The characterization results indicate that the WPU showed poor solubility in ethanol causing low distribution uniformity of IF-WS2 and WPU on fibers. Comparable mechanical properties were obtained for the optimal samples prepared with water and water/ethanol mediums. The maximum load, energy to break, and normalized energy to break increased by 26.5%, 44.9%, and 31.1% for the 2 wt% IF-WS2/10 wt% WPU/UHMWPE composite prepared with water medium, respectively. Neat UHMWPE fibers showed failure mechanisms of fiber breakage, delamination, fibrillation, and splitting, while additional ductile breakage and matrix debonding were observed on WPU/IF-WS2 incorporated UHMWPE composites.